Research Burden of Interstitial Lung Diseases in Turkey – RBILD: Interstitial Lung Diseases in Turkey - Aycicek, Olcay; Cetinkaya, Erdogan; Demirci Ucsular, Fatma; Bayram, Nazan; Senyigit, Abdurrahman; Aksel, Nimet; Atilla, Nurhan; Sarioglu, Nurhan; Niksarlioglu, Elif Yelda; Ilgazli, Ahmet; Kilic, Talat; Gunbatar, Hulya; et al. (Sarcoidosis, Vasculitis and Diffuse Lung Diseases, 2022)
Introduction:The aim of our study is to investigate the etiological distribution of ILD in Turkey by stratifying the epidemiological characteristics of ILD cases, and the direct cost of initial diagnosis of the diagnosed patients. Material-Method:The study was conducted as a multicenter, prospective, cross-sectional, clinical observation study. Patients over the age of 18 and who accepted to participate to the study were included and evaluated as considered to be ILD. The findings of diagnosis, examination and treatment carried out by the centers in accordance with routine diagnostic procedures were recorded observationally. Results:In total,1070 patients were included in this study. 567 (53%) of the patients were male and 503 (47%) were female. The most frequently diagnosed disease was IPF (30.5%). Dyspnea (75.9%) was the highest incidence among the presenting symptoms.Physical examination found bibasilar inspiratory crackles in 56.2 % and radiological findings included reticular opacities and interlobular septal thickenings in 55.9 % of the cases.  It was observed that clinical and radiological findings were used most frequently (74.9%) as a diagnostic tool. While the most common treatment approacheswere the use of systemic steroids and antifibrotic drugs with a rate of 30.7% and 85.6%, respectively. The total median cost from the patient’s admission to diagnosis was 540 Turkish Lira. ConclusionWe believe that our findings compared with data from other countries will be useful in showing the current situation of ILD in our country to discuss this problem and making plans for a solution.